Liver fibrosis occurs through dysregulation of MyD88‐dependent innate B‐cell activity. Issue 6 (25th March 2015) - Thapa, Manoj; Chinnadurai, Raghavan; Velazquez, Victoria M.; Tedesco, Dana; Elrod, Elizabeth; Han, Jin‐Hwan; Sharma, Prachi; Ibegbu, Chris; Gewirtz, Andrew; Anania, Frank; Pulendran, Bali; Suthar, Mehul S.; et al.
<x xml:space="preserve">Abstract</x> Chronic liver disease mediated by activation of hepatic stellate cells (HSCs) leads to liver fibrosis. Here, we postulated that the immune regulatory properties of HSCs might promote the profibrogenic activity of B cells. Fibrosis is completely attenuated in carbon tetrachloride–treated, B cell–deficient µMT mice, showing that B cells are required. The retinoic acid produced by HSCs augmented B‐cell survival, plasma cell marker CD138 expression, and immunoglobulin G production. These activities were reversed following addition of the retinoic acid inhibitor LE540. Transcriptional profiling of fibrotic liver B cells revealed increased expression of genes related to activation of nuclear factor κ light chain enhancer of activated B cells, proinflammatory cytokine production, and CD40 signaling, suggesting that these B cells are activated and may be acting as inflammatory cells. Biological validation experiments also revealed increased activation (CD44 and CD86 expression), constitutive immunoglobulin G production, and secretion of the proinflammatory cytokines tumor necrosis factor‐α, monocyte chemoattractant protein‐1, and macrophage inflammatory protein‐1α. Likewise, targeted deletion of B‐cell‐intrinsic myeloid differentiation primary response gene 88 signaling, an innate adaptor with involvement in retinoic acid signaling, resulted in reduced infiltration of migratory CD11c+ dendritic cells and Ly6C++ monocytes and, hence, reduced liver pathology. Conclusion: Liver fibrosis occurs through a mechanism of HSC‐mediated augmentation of innate B‐cell activity. These findings highlight B cells as important "first responders" of the intrahepatic immune environment. (Hepatology 2015;61:2067‐2079)